2016
DOI: 10.2147/hp.s101133
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen days of 3,200 m simulated hypoxia marginally regulates markers for protein synthesis and degradation in human skeletal muscle

Abstract: Chronic hypoxia leads to muscle atrophy. The molecular mechanisms responsible for this phenomenon are not well defined in vivo. We sought to determine how chronic hypoxia regulates molecular markers of protein synthesis and degradation in human skeletal muscle and whether these regulations were related to the regulation of the hypoxia-inducible factor (HIF) pathway. Eight young male subjects lived in a normobaric hypoxic hotel (FiO2 14.1%, 3,200 m) for 15 days in well-controlled conditions for nutrition and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…There were also no differences between phases in the enzymatic activities of the catalytic subunits of the 26S proteasome, an additional indication that muscle proteolysis was not significantly influenced by HA or the combination of chronic HA and severe energy deficit. In agreement with findings from our study, MuRF1 mRNA expression was lower in humans who were exposed to HA at 3200 m for 15 d compared with SL, with no other changes in the markers of proteolysis between phases (50). Similarly, D'Hulst et al previously reported lower postprandial 26S proteasome activity under acute HA conditions compared with SL (49).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There were also no differences between phases in the enzymatic activities of the catalytic subunits of the 26S proteasome, an additional indication that muscle proteolysis was not significantly influenced by HA or the combination of chronic HA and severe energy deficit. In agreement with findings from our study, MuRF1 mRNA expression was lower in humans who were exposed to HA at 3200 m for 15 d compared with SL, with no other changes in the markers of proteolysis between phases (50). Similarly, D'Hulst et al previously reported lower postprandial 26S proteasome activity under acute HA conditions compared with SL (49).…”
Section: Discussionsupporting
confidence: 92%
“…By d 21, chronic HA exposure while being severely underfed manifested in a complete suppression of mTORC1mediated anabolic signaling in response to both exercise and protein ingestion. Two previous human investigations (50,51) reported little or no change in mTORC1-mediated anabolic signaling under basal conditions after 7-15 d of altitude exposure at 3200-4600 m, but, to the best of our knowledge, no human study has examined the acute anabolic signaling response to exercise and protein feeding after chronic HA exposure combined with severe energy deficit. Several investigations, using stable isotope methodologies, have consistently demonstrated that shortterm (,21 d) moderate energy deficit (;20-40%) reduces rates of basal skeletal muscle protein synthesis (13)(14)(15)(16)(17) and blunts synthetic response to a protein-containing meal (17,18) at SL.…”
Section: Discussionmentioning
confidence: 94%
“…In hypoxic conditions, HIF-1α migrates to the nucleus and transcribes target genes such as BNIP3 [ 28 ]. Therefore, increased BNIP3 expression indicates enhanced transcriptional activity of HIF-1α [ 29 31 ]. We observed increased BNIP3 mRNA (Figure 7 ) and protein (Figure 8 ) levels in the cisplatin treatment group.…”
Section: Discussionmentioning
confidence: 99%
“…vascular endothelial growth factor (VEGF; ‐66%)] (D'Hulst et al . ), absence of muscle angiogenesis as well as marginal changes in oxidative enzymes [e.g. citrate synthase (CS)] (Lundby et al .…”
mentioning
confidence: 99%
“…Specifically, downregulation of HIF-1a (-49%) and its target genes [e.g. vascular endothelial growth factor (VEGF; -66%)] (D'Hulst et al 2016), absence of muscle angiogenesis as well as marginal changes in oxidative enzymes [e.g. citrate synthase (CS)] (Lundby et al 2009) have been reported.…”
mentioning
confidence: 99%